”Suspeitei desde o princípio!”: a (re)leitura dos clássicos pelas paródias do seriado Chapolin - SILVA, Patrícia Vieira da (2015)
In this work, taking television as an important instrument democratizer of access to erudite cultural goods, it is proposed to analyze the (re) reading of classics of universal literature, namely Faust, a tragedy of Goethe; Cyrano de Bergerac, by Rostand; Don Juan Tenorio, of Zorrilla; and Romeo and Shakespeare's Juliet, by the parodies of the popular humorous series Chapolin present in the episodes "According to the Devil" (1976), "Cyrano de Bergerac" (1978), "The Story of Don Juan Tenório" (1978) and "The Romantic Story of Julio and Rumieta, parts 1 and 2 "(1979), respectively.From the theory of adaptation postulated by Stam (1992, 2000, 2006, 2008, 2013), Hutcheon (2013) and Sanders (2006), it is discussed, in this dissertation, how the adaptations of the classics were built, trying to highlight the creative processes involved in the act of adaptation in the light of the concepts of dialogism (BAKHTIN, 1997, 2000), intertextuality (KRISTEVA, 2005) and hypertextuality (GENETTE, 1997, 2010), in confluence with the different nuances of the concept of parody discussed by Bakhtin (1993, 1997), Sant'Anna (2003), Hutcheon (1985) and Rose (1993). Seeking out the inter / hypertextual references present in the parodic adaptations, as well as the new elements, incorporated to meet the proposal of the humorous program, far from being based on criteria of fidelity - which would lead to looking for betrayals and / or deformations made by the text of arrival in relation to the source text, proposal rejected in this research ─, it is demonstrated, through the analysis of the corpus, that all text is palimpsestic by nature and that even the works that served as inspiration for the analyzed episodes are, themselves, re-readings of others. While understanding such adaptations as new products, which works to break with them, adapting them to their main objective ─ the production of the comic effect ─ and the space and format of this kind of program television, one concludes that, at the same time that they deacratize the classics, through the humor, the irony, the satire and the jocular ridicule used, the parodies serials help keep these literary texts alive and by their revival in the memory of those who already know them, and by their to those who have not yet had access to them.